Former les enseignants à soutenir l’autonomie de leurs élèves : le rôle de l’analyse vidéo - Amael André; Samuel Hamon; Matthieu Laville; Guillaume Ruelland (Éducation et Socialisation)
Based on a mixed methodology, this article aims, on the one hand, to examine the effects of a training system based on video analysis in peer groups on the evolution of motivational style of beginning teachers. On the other hand, it aims to identify the key elements of this training from the point of view of the trainees. The e results indicate that the training significantly affects the development of teachers' autonomy-support. In addition, the qualitative results highlight three key elements of the training responsible for the changes: the video analysis, the collaborative group based on the sharing of resources and the duration of the training over a school year.